Peningkatan Kompetensi Guru Sekolah Dasar Dalam Pengembangan Rencana Pelaksanaan Pembelajaran (RPP) Daring di SDN Margorejo I Kota Surabaya Provinsi Jawa Timur - Fanny, Arif Mahya; Satianingsih, Rarasaning; Rusminati, Susi Hermin; Fanani, Achmad; Prastyo, Danang (Manggali, 2021)
The Covid-19 outbreak has become a pandemic and its massive and relatively fast spread has made various elements change their patterns of life, without exception the world of education. The world of education changes the pattern of the learning system. Changes in learning patterns from face-to-face learning to online learning force teachers to learn quickly. One of them is making an online Learning Implementation Plan (RPP). For this reason, the lecturer team of the PGSD Study Program at the PGRI Adi Buana University Surabaya considers that it is important to carry out the Training to Improve the Competence of Primary School Teachers in the Development of Online Learning Implementation Plans (RPP). The target of this Community Service is teachers at SDN Margorejo I Surabaya City, East Java. The implementation of Community Service (PPM) activities is carried out online through the zoom meeting application. This activity was carried out in September 2020. This Community Service Activity was carried out in the form of training and workshops starting with material exposure, discussions and workshops with lecturer assistance during group work. Implementation of the Community Service program PGSD Study Program at the University of PGRI Adi Buana Surabaya can solve the problem of preparing and developing an Online Learning Implementation Plan. Keysword: Development, workshops, Online Learning Implementation Plan, Covid-19.